1993
DOI: 10.1021/ma00062a019
|View full text |Cite
|
Sign up to set email alerts
|

Thin-film behavior of poly(methyl methacrylates). 6. Monolayer phase behavior in relation to stereocomplexation in mixed monolayers of i- and s-PMMA

Abstract: The stereocomplexation process in mixed monolayers of isotactic and syndiotactic poly(methy1 methacrylate) is efficient only when low molecular weight samples are used. This phenomenon can be explained by an increasing tendency for phase separation in the monolayer upon using higher molecular weight samples, leading to larger domain sizes and a limited mutual accessibility: especially the use of high molecular weight syndiotactic PMMA appears to result in strong aggregation processes of these chains caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Stereocomplexation of polymers at the air/ water interface has only been studied only for polylactides 35,36 and for PMMA. [37][38][39][40][41][42] Indeed, Brinkhuis and Schouten have shown that a stereocomplex could be formed at the air/water interface by compressing a Langmuir film of a 2:1 isotactic:syndiotactic PMMA blend. [39][40][41] This stereocomplex consists of double-helical structures with a syndiotactic strand winding around an isotactic strand, the stoichiometry being 2:1 at the monomeric level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stereocomplexation of polymers at the air/ water interface has only been studied only for polylactides 35,36 and for PMMA. [37][38][39][40][41][42] Indeed, Brinkhuis and Schouten have shown that a stereocomplex could be formed at the air/water interface by compressing a Langmuir film of a 2:1 isotactic:syndiotactic PMMA blend. [39][40][41] This stereocomplex consists of double-helical structures with a syndiotactic strand winding around an isotactic strand, the stoichiometry being 2:1 at the monomeric level.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to polylactides (PLA), stereocomplexation has also been reported for different polymer couples, the most studied of them being poly(α-methyl-α-ethyl-β-propiolactones), poly(γ-benzyl glutamates), and poly(methyl methacrylates) (PMMA). Stereocomplexation of polymers at the air/water interface has only been studied only for polylactides , and for PMMA. Indeed, Brinkhuis and Schouten have shown that a stereocomplex could be formed at the air/water interface by compressing a Langmuir film of a 2:1 isotactic:syndiotactic PMMA blend. This stereocomplex consists of double-helical structures with a syndiotactic strand winding around an isotactic strand, the stoichiometry being 2:1 at the monomeric level.…”
Section: Introductionmentioning
confidence: 99%
“…Typical stereoregular poly(methyl methacrylate)s (PMMAs), i.e., isotactic ( it -) and syndiotactic ( st -) PMMAs, are known to associate in the solid state and specific solutions to form a crystalline polymer complex, i.e., a stereocomplex, in which inner single or double helixes of the it -PMMA chain are surrounded by an outer st -PMMA helical chain with a larger radius [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. The unique structures and properties of synthetic polymers have attracted attention from both fundamental and application viewpoints [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Furthermore, these stereoregular polymer chains have been incorporated into various well-defined polymers, such as block, star, graft, and end-functionalized polymers, to create novel properties and functions [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…17 Research on Langmuir-Blodgett (LB) films of polymers has increased drastically in the past decade because of possible applications in nonlinear optical devices and other fields such as biosensors and microlithography. Meanwhile, the stereocomplexation of a polymer at the air-water interface had been studied in great detail for poly(methyl methacrylate) (PMMA), [18][19][20][21] which is another typical example of a macromolecular stereocomplex. Indeed, Brinkhuis et al [18][19][20][21] have shown that the stereocomplex could form at the air-water interface by compressing a Langmuir film of a 2:1 isotactic/ syndiotactic PMMA blend.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the stereocomplexation of a polymer at the air−water interface had been studied in great detail for poly(methyl methacrylate) (PMMA), which is another typical example of a macromolecular stereocomplex. Indeed, Brinkhuis et al have shown that the stereocomplex could form at the air−water interface by compressing a Langmuir film of a 2:1 isotactic/syndiotactic PMMA blend. This stereocomplex consists of double-helical structures with a syndiotactic strand winding around an isotactic strand.…”
Section: Introductionmentioning
confidence: 99%